2018
DOI: 10.1080/21645515.2018.1537744
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness ofHaemophilus influenzaetype b vaccination after splenectomy - impact on selected immunological parameters

Abstract: Splenectomy is a surgery indicated in case of splenic rupture after injury, when there are tumors in the spleen, or as a treatment for certain diseases, such as idiopathic thrombocytopenic purpura and spherocytosis. The aims of the study were to assess the immunological response to the Haemophilus influenzae type b (Hib) vaccine and the post-vaccination changes in lymphocyte subsets and cell activation markers in splenectomized patients and healthy volunteers. Blood samples were collected from 25 patients that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…3,13 While vaccination is essential for optimal protection against COVID-19 infection in healthy individuals, 12 it is not clear whether they are effective in patients with TDT, given the possibility of an altered ability to produce Abs (especially in patients who have undergone splenectomy) due to a possible imbalance between Th17 and regulatory T cells. 13,14 In our study, patients with TDT showed a similar ability to produce NAbs and IgG Abs against the S-RBD of SARS-CoV-2 after the first and second doses of the BNT162b2 and mRNA-1273 vaccines compared to healthy controls. The safety profile of vaccination in the general population has revealed some serious side-effects, including Bell's palsy, myocarditis/pericarditis, cerebral venous sinus thrombosis, stroke, and thrombocytopenia.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…3,13 While vaccination is essential for optimal protection against COVID-19 infection in healthy individuals, 12 it is not clear whether they are effective in patients with TDT, given the possibility of an altered ability to produce Abs (especially in patients who have undergone splenectomy) due to a possible imbalance between Th17 and regulatory T cells. 13,14 In our study, patients with TDT showed a similar ability to produce NAbs and IgG Abs against the S-RBD of SARS-CoV-2 after the first and second doses of the BNT162b2 and mRNA-1273 vaccines compared to healthy controls. The safety profile of vaccination in the general population has revealed some serious side-effects, including Bell's palsy, myocarditis/pericarditis, cerebral venous sinus thrombosis, stroke, and thrombocytopenia.…”
Section: Discussionsupporting
confidence: 54%
“…Patients with TDT are considered at high risk of developing severe infection with SARS‐CoV‐2 due altered immunity and frequent comorbidities 3,13 . While vaccination is essential for optimal protection against COVID‐19 infection in healthy individuals, 12 it is not clear whether they are effective in patients with TDT, given the possibility of an altered ability to produce Abs (especially in patients who have undergone splenectomy) due to a possible imbalance between Th17 and regulatory T cells 13,14 . In our study, patients with TDT showed a similar ability to produce NAbs and IgG Abs against the S‐RBD of SARS‐CoV‐2 after the first and second doses of the BNT162b2 and mRNA‐1273 vaccines compared to healthy controls.…”
Section: Discussionmentioning
confidence: 63%
“…Thus, we studied the different T cell subsets and found no changes in the various T-cell subsets compared with controls, with the exception of an increase in circulating Th17 cells and CD8 + TCMs. This increase in the percentages of CD8 + TCM in splenectomized patients [15] have rarely been reported but they could partially correct the memory B-cell de ciency in splenectomized patients regarding the anti-infectious immune response as demonstrated in an experimental model [16]. The higher risk of infections by encapsulated bacteria is also attributed to impaired production by marginal zone B cells of capsular polysaccharide-speci c IgM and IgG [17] and reduced IgM memory B cells [18].…”
Section: Discussionmentioning
confidence: 90%
“…Rates of overwhelming sepsis have been reported to be approximately 3‐4% with a reported mortality rate of 1.4% 32‐35 . Inadequate immunization following vaccination in asplenic patients is also a concern as studies have shown decreased levels of circulating antibodies and T cells following vaccination in postsplenectomy patients 36,37 . Prior to planned splenectomy, vaccination for encapsulated organisms (ie, Streptococcus pneumoniae (pneumococcus), Haemophilus influenzae type b (Hib), and Neisseria meningitides ) should be completed 38,39 .…”
Section: Complications Of Splenectomymentioning
confidence: 99%